2020
DOI: 10.18502/jfqhc.7.1.2448
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality of Ready-to-Eat Street Vended Food Groups Sold in the Johannesburg Metropolis, South Africa

Abstract: Background: In many developing countries, the risk of contracting a food-borne disease is high after consuming contaminated ready-to-eat Street-Vended Foods (SVFs). The main objective of this research was to assess the microbiological quality of SVF groups sold in the Johannesburg Metropolis, South Africa. Methods: A stratified random sampling procedure was used for collecting the ready-toeat SVF samples. Methods prescribed by the International Organization for Standardization (ISO) were used for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…In the present study microbiologic cultures were done for all studied samples, among 100 enrolled samples, microorganisms were isolated from 73% (73/100), while 27% (27/100) revealed no growth, this agreement with, Yusha'u et al [23]. On the other hand, higher rate of isolation was observed by Asiegbu et al [24] in the Johannesburg, South Africa who found an isolation rate of 85.37%. The difference can be explained by the informal setting that is usually known for unhygienic operating environment.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study microbiologic cultures were done for all studied samples, among 100 enrolled samples, microorganisms were isolated from 73% (73/100), while 27% (27/100) revealed no growth, this agreement with, Yusha'u et al [23]. On the other hand, higher rate of isolation was observed by Asiegbu et al [24] in the Johannesburg, South Africa who found an isolation rate of 85.37%. The difference can be explained by the informal setting that is usually known for unhygienic operating environment.…”
Section: Discussionsupporting
confidence: 83%
“…Vendors should collaborate during inspections, permit applications, and compliance checks to ensure that specified standards and regulations are followed. ( Asiegbu et al,2020).…”
Section: Role Of Food Vendors In Mitigating Risks and Hazardsmentioning
confidence: 99%
“…More recently, Asiegbu et al [32] have come to the conclusion that the microbial quality and safety of ready-to-eat sold in the Johannesburg Metropolis remain a serious public health concern. Indeed, studying hygienic quality of street food sold in Johannesburg Metropolis (South Africa), their result showed that of the 205 ready-to-eat street-vended foods samples, 85.37% had aerobic growth.…”
Section: Evidence On Microbiological Characteristics Of Street Food In Africamentioning
confidence: 99%